Superior Patellar Dislocation Misdiagnosed as Patellar Tendon Rupture: The Value of Ultrasonography - Artit Boonrod; Sermsak Sumanont; Manusak Boonard; Arunnit Boonrod (Case Reports in Orthopedics)
Superior dislocation of the patella with intact patellar tendon is a rare condition. Most cases in literatures were diagnosed by clinical examination and plain radiography; however there are many cases that were misdiagnosed as patellar tendon rupture. In this case, we demonstrate the use of ultrasound for diagnosis of superior dislocation of the patella in the emergency department. We also include a literature review of similar cases and discuss the advantages of different types of imaging for diagnosis in this condition.